Probable case of spotted fever group rickettsial infection in a new suspected endemic area, Colombia (2017)
Spoted fever group (SFG) rickettsioses are actually considered as emerging and re-emerging zoonotic diseases, caused by pathogenic bacteria of the spotted fever group rickettsiae (SFGR). Recently, serologic studies in human and animals conducted in Colombian Orinoquia, showed a high seroprevalence against SFGR. In June 2015, a 50-year-old male was admitted to a hospital in Bogotá, Colombia, with two days of malaise and temperature of 39 °C, associated to generalized rash 24 h after the onset of fever. He referred a work visit and outdoor activities in rural area of the Department of Meta 15 days prior the onset of symptoms. The patient was transferred to the intensive care unit with supplementary oxygen, inotropic support and was assessed by the infectious diseases department, indicating the addition of Doxycycline. After seven days of antibiotic treatment the patient was discharged with no evidence of new symptoms or sequels. Retrospectively, two serum samples collected during the acute and convalescent phase were evaluated; there was four fold rise in titer against SFGR. With the foregoing, associated with the recent serological evidence that suggests the circulation of SFGR species in the Colombian Orinoquia, we consider to recognize this region as a new endemic area for SFG Rickettsioses.